A model to address healthcare gaps and poor research participation in Hispanic patients with Parkinson's disease - Ghilardi, M. Felice; Di Rocco, Alessandro; Fearday, Jennifer; Sperlakis, Donna; Lima, Maria; Vanegas-Arroyave, Nora; Tatti, Elisa; Arroyave, Marcelo; Stevens, Evelyn; Hernandez, Denise; Latapi-Gonzalez, Paulina; Deoudes, Meri-Margaret; et al. (Frontiers in Aging Neuroscience, 2025)
Parkinson's disease (PD), a progressive neurodegenerative disorder, manifests with motor and non-motor symptoms. Despite similar incidence, in the US, disease management of Hispanic patients with PD is poorer than that of White non-Hispanics, and their participation in clinical trials does not reflect expected values (well below 5% vs. expected values around 20%). Together with other evidence, these observations are expressions of poor healthcare in Hispanic patients with PD, suggesting underutilization of proper healthcare, social and economic disadvantage, and other factors. The scant participation of Hispanic patients in clinical trials further exacerbates care inadequacy. In this paper, after reviewing evidence of healthcare gaps in Hispanic patients with PD and their low participation in research, we present a comprehensive model for reaching these patients and their caregivers, educating them on PD, and engaging them in research. This model is based on the work and experience of the Parkinson's Foundation, which over the years, has worked to increase PD awareness in Hispanic communities. This model is based on the training of promotores de salud (community health workers) inside Hispanic communities, the identification of needs and priorities of patients and caregivers with surveys and focus groups within Hispanic communities, and the patients' feedback about their participation in research. The development of this model could achieve sustainable partnerships with community-based organizations to promote better care and enhance participation in research of Hispanic patients. In turn, this could lead to a better quality of life for all patients with PD and their caregivers.